DNA methylation-based classification and grading system for meningioma: a multicentre, retrospective analysis - Sahm, Felix; Schrimpf, Daniel; Kölsche, Christian; Reuss, David; Capper, David; Sturm, Dominik; Reinhardt, Annekathrin; Huang, Kristin; Wefers, Annika K.; Jungk, Christine; Drüschler, Katharina; Seiz-Rosenhagen, Marcel; et al. (The lancet. Oncology, 2017)
The WHO classification of brain tumours describes 15 subtypes of meningioma. Nine of these subtypes are allotted to WHO grade I, and three each to grade II and grade III. Grading is based solely on histology, with an absence of molecular markers. Although the existing classification and grading approach is of prognostic value, it harbours shortcomings such as ill-defined parameters for subtypes and grading criteria prone to arbitrary judgment. In this study, we aimed for a comprehensive characterisation of the entire molecular genetic landscape of meningioma to identify biologically and clinically relevant subgroups.